2009
DOI: 10.1038/gene.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

The rat antigen-presenting lectin-like receptor complex influences innate immunity and development of infectious diseases

Abstract: Genetic variation in the antigen-presenting lectin-like receptor gene complex (APLEC) associates with autoimmunity and arthritis in rats and humans. We hypothesized that the encoded C-type lectin-like receptors might influence innate immunity and responses to infectious agents. To test this hypothesis, we compared in vivo and in vitro phenotypes in DA rats and APLEC-congenic rats. Survival rates following infection with Staphylococcus aureus and Herpes simplex virus differed significantly between the two strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
3
13
1
Order By: Relevance
“…However, Hse1 was confirmed as the main disease regulating region by infecting congenic lines. The antigen-presenting lectin-like receptor gene complex (APLEC) located towards the end of chromosome 4 was previously reported to have a disease regulatory effect in a different model of HSV-1-induced encephalitis in the DA strain [15]. However, in this present study by infecting R17 congenic [24] rats with HSV-1, we could not confirm any HSE regulation by the APLEC genes region.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, Hse1 was confirmed as the main disease regulating region by infecting congenic lines. The antigen-presenting lectin-like receptor gene complex (APLEC) located towards the end of chromosome 4 was previously reported to have a disease regulatory effect in a different model of HSV-1-induced encephalitis in the DA strain [15]. However, in this present study by infecting R17 congenic [24] rats with HSV-1, we could not confirm any HSE regulation by the APLEC genes region.…”
Section: Discussioncontrasting
confidence: 91%
“…None of the rats developed symptoms, demonstrating the protective role of the PVG alleles in the Hse1 region (Figure 3). For both mapping and control purposes, we furthermore tested HSE susceptibility in a set of congenic lines with different chromosome 4 congenic PVG fragments on the DA background; R2:DA.PVG (D4Rat23–D4Rat108), R11:DA.PVG (D4Rat103 – D4Mit12), R21:DA.PVG (OT40.07 – D4Mit12) covering the experimental autoimmune encephalomyelitis (EAE) QTLs Eae24–Eae27 [14] and R17 (D4Kiru12–D4Kiru55) covering the APLEC genes region that are associated with arthritis and autoimmunity in rats and humans [15] (Figure 3). All of these lines are homozygous for DA alleles in Hse1 .…”
Section: Resultsmentioning
confidence: 99%
“…Especially the increased TNFa production stands in discrepancy to other studies, where TNFa appears to be a mediator of joint inflammation. 23 However, our findings are in agreement with data from Guo et al, 24 where they found an enhanced IL-6 secretion of Oia2 congenic macrophages following LPS stimulation. It also confirms data from a mutant DA rat, which is protected from PIA, CIA and experimental allergic encephalomyelitis yet shows enhanced cell proliferation and Th1 cytokine production as well as an increased number of activated T cells (unpublished data).…”
Section: Discussionsupporting
confidence: 78%
“…Its precise role and function are not completely understood, but we and others have previously identified a cluster of C-type lectin receptor genes including DCIR that regulates arthritis susceptibility and influences the development of infectious diseases in rat [11], [12]. DCIR knockout (DCIR-KO) mice showed a markedly exacerbated response to collagen-induced arthritis, and aged DCIR-KO mice spontaneously developed sialadenitis and enthesitis with elevated levels of autoantibodies [13].…”
Section: Introductionmentioning
confidence: 99%